P2Y receptors in Alzheimer's disease. (13th October 2014) - Erb, Laurie; Cao, Chen; Ajit, Deepa; Weisman, Gary A.
Review Alzheimer's disease (AD) involves the formation of plaques composed of beta‐amyloid peptides (Aβ) and neuronal death in brain regions responsible for learning and memory. In recent years, Aβ has been shown to affect ATP release from brain and blood cells and alter the expression of G protein‐coupled P2Y receptors that respond to ATP and other nucleotides. Accumulating evidence reveals a prominent role for P2Y receptors in AD pathology, including Aβ metabolism, neuroinflammation, neuronal function and cerebral blood flow. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>